2019
DOI: 10.1167/iovs.19-26893
|View full text |Cite
|
Sign up to set email alerts
|

Lens Stretching Modulates Lens Epithelial Cell Proliferation via YAP Regulation

Abstract: PURPOSE. The continuous growth of the lens throughout life may contribute to the onset of age-related conditions in the lens (i.e., presbyopia and cataract). Volumetric growth is the result of continuous proliferation of lens epithelial cells (LECs). The driving factors controlling LEC proliferation are not well understood. This study tested the hypothesis that mechanical stretching modulates LEC proliferation. METHODS. Biomechanical regulation of LEC proliferation was investigated by culturing whole porcine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 63 publications
2
21
0
Order By: Relevance
“…121,122 Additionally, simulating accommodative forces in whole porcine lens cultures in vitro has been found to induce mitotic activity in the lens epithelium. 123 posterior capsule and PCO. 124,125 Cataract surgery is known to alter LEC proliferation and disrupt both the biochemical and biomechanical homeostasis of the lens.…”
Section: Lec Mediated Lens Regenerationmentioning
confidence: 99%
“…121,122 Additionally, simulating accommodative forces in whole porcine lens cultures in vitro has been found to induce mitotic activity in the lens epithelium. 123 posterior capsule and PCO. 124,125 Cataract surgery is known to alter LEC proliferation and disrupt both the biochemical and biomechanical homeostasis of the lens.…”
Section: Lec Mediated Lens Regenerationmentioning
confidence: 99%
“…Additionally, whole tissue culture of lenses has allowed for the emergence of lens mechanobiology. We demonstrated how tissue-scale mechanical loads are transmitted onto lens epithelial cells [15 , 16] ; moreover, others have demonstrated that whole lens stretch results in lens epithelial cell proliferation [16] . Furthermore, the ex vivo culture system has allowed for the study of lens EMT [4 , 5 , 7 , [17] , [18] , [19] .…”
Section: Methods Detailsmentioning
confidence: 80%
“…The ex vivo culture of intact, isolated lenses is a powerful method to study lens epithelial cell biology and pathology [7 , 15 , 16] . As compared to two-dimensional culture of lens epithelial derived cells or cell lines, whole lens culture allows for preservation of lens/cellular structures.…”
Section: Methods Detailsmentioning
confidence: 99%
“…A recent paper showed the feasibility of culturing whole lenses in vitro, which might solve the problems of nonbiological substrate and the lack of lens capsule for lens cells. 76 Future studies will build on these findings by using whole lens culture models, quantifying intercellular levels of the antioxidants, evaluating the effects of these antioxidants on endogenous cellularly produced ROS levels, and quantifying the concentrations of the reduced and oxidized forms of vitamin C and glutathione in a hypoxic environment that better mimics in vivo conditions. A limitation of this study was measurement of ROS using a DCF assay rather than hydrogen peroxide directly.…”
Section: Figure 5 Glutathione Prolonged the Antioxidant Activity Of Vitamin C Up To 3 Days After Incubationmentioning
confidence: 99%